Hypermethylation of estrogen receptor promoter region in adult testis of rats exposed neonatally to bisphenol A - Doshi, Tanvi; Mehta, Smita Salian; Dighe, Vikas; Balasinor, Nafisa; Vanage, Geeta (Toxicology (Amsterdam), 2011)
Bisphenol A (BPA) is an estrogenic endocrine disruptor commonly used in manufacture of polycarbonate plastics and epoxy resins. Due to its ubiquitous presence in the environment, health concerns are increasing. Earlier studies from our group have shown that neonatal exposure of male rats to BPA affected spermatogenesis leading to impairment in fertility during adulthood. Further we also observed an altered gene expression of ERα and ERβ in adult testis upon BPA exposure. Based on these results, we hypothesized that apart from endocrine action, BPA might mediate perturbations in expression of ERs via epigenetic mechanism. The present study was undertaken to determine the effect of exposure of neonatal male rats to BPA on DNA methylation profile of estrogen receptor promoter region and on DNA methylation machinery. In order to test this hypothesis, neonatal male rats were subcutaneously injected with 2.4 μg of BPA/day for the first five days of life, i.e., on postnatal days (PND) 1–5, while control group received vehicle (sesame oil). Animals were sacrificed during adulthood (PND-125) and testes were dissected out for analysis. Methylation pattern of promoter region of ERα and ERβ was analyzed in the testis by bisulfite sequencing and expression levels of DNA methyltransferases by quantitative RT-PCR and Western blotting respectively. Bisulfite sequencing revealed significant hypermethylation of ERα promoter to varying extents from 40% to 60%, and ERβ promoter region with varying extent from 20% to 65%. Approximately 2-fold increase in Dnmt3a and Dnmt3b expression at transcript and protein level was also observed. The experimental evidence demonstrated that the neonatal exposure of rats to BPA led to aberrant DNA methylation in testis, indicating methylation mediated epigenetic changes as one of the possible mechanisms of BPA induced adverse effects on spermatogenesis and fertility.